2009
DOI: 10.1007/s11250-009-9326-7
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the functions of village goats in Zimbabwe and South Africa

Abstract: The objective of the study was to compare the functions and management systems of goats in Chirumanzu district in Zimbabwe and, Alfred Nzo and Amatole districts in the Eastern Cape Province of South Africa. Data were collected using participatory rural appraisal techniques and direct observations. In addition, structured questionnaires from 344 households as follows; 69 from Alfred Nzo district, 144 from Amatole district and 132 from Chirumanzu district were also used to retrieve information from farmers. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Forage starts to diminish in quality and quantity with time into the dry season. Many studies have reported fluctuations in quality and quantity of forage with season and this consequently affects the performance of livestock species on semiarid rangelands (Berhane and Eik, 2006;De Vries, 2008;Rumosa Gwaze et al, 2009a). Under-performance of livestock on rangelands is marked during the dry season compared to the wet season.…”
Section: Introductionmentioning
confidence: 99%
“…Forage starts to diminish in quality and quantity with time into the dry season. Many studies have reported fluctuations in quality and quantity of forage with season and this consequently affects the performance of livestock species on semiarid rangelands (Berhane and Eik, 2006;De Vries, 2008;Rumosa Gwaze et al, 2009a). Under-performance of livestock on rangelands is marked during the dry season compared to the wet season.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that goat sales occurred mainly during ceremonial periods (June and December) indicates the relative importance attached to ceremonies, especially the rite of passage for boys and this is confirmed by Rumosa Gwaze et al (2009a). Besides being a traditional ceremony period, December is a festive season and the demand for meat is high (Masika and Mafu 2004).…”
Section: Discussionmentioning
confidence: 90%
“…Communal goats fulfill multiple roles that include provision of meat, manure, milk, and cash from sales of the goats and their by-products (Homann et al 2007;Rumosa Gwaze et al 2009a). Their contribution to household economies is, however, poorly understood with the assumption that it is similar across communities, production systems, and flock sizes (Verbeek et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Goat production on natural range is one of the main sources of income for peasants in many developing countries with arid and semiarid zones (Davran et al, 2009;Rumosa Gwaze et al, 2009). Because of severe overgrazing and the low and seasonal rainfall in these areas, natural forage resources fluctuate greatly in quantity and quality throughout the year (Manzano et al, 2000).…”
Section: Introductionmentioning
confidence: 99%